An ultra-sensitive core-sheath fiber strain sensor based on double strain layered structure with cracks and modified MWCNTs/silicone rubber for wearable medical electronics. (5th January 2023) - Wu, Shunge; Liu, Ping; Tong, Wei; Li, Junliang; Xu, Guangyuan; Teng, Fei; Liu, Jian; Feng, Han; Hu, Ruohai; Yang, Austin; Liu, Caixia; Xing, Kun; et al.
Abstract: Flexible resistive sensors have attracted widespread attention in the field of wearable electronics. Inspired by the single-layer crack structure which has ultra-high sensitivity, a double strain layered crack structure is proposed to expand the maximum working strain (30%) of flexible sensor while maintaining the ultra-high sensitivity (GF = 2165 at 0–30% and 7381 at 25–30%). MWCNTs modified by 3-Aminopropyltriethoxysilane were filled into silicon rubber to form nanocomposites with fast response times (42 ms), high repeatability (>1000) and low hysteresis (7.08%). Furthermore, the respiratory rate, heart rate and blood pressure can be measured by the proposed sensor. The average errors of the respiratory rate and heart rate are less than 2% and 3% respectively. The mean error of systolic blood pressure, diastolic blood pressure and mean blood pressure is −0.0042 mmHg, 0.3730 mmHg, and 0.2472 mmHg respectively, meeting the standards of Association for the Advancement of Medical Instrumentation and A-level British Hypertension Society. This study shows that the proposed sensor has broad application prospects in high-precision wearable medical electronics. Graphical abstract: Image 1